Developing visitor thresholds of sound from shale natural gas compressors for motorized and non-motorized recreation users in Pennsylvania State Forests. (1st January 2020) - Miller, Zachary D.; Ferguson, Lauren A.; Newman, Peter; Ferguson, Michael; Tipton, Nathan; Sparrow, Victor; Taff, B. Derrick
Highlights: Visitor experiences related to sounds from natural gas compressors are examined. Threshold models are used to understand visitor experience over varying conditions. Motorized and non-motorized visitors have significantly different thresholds. Non-motorized users find sounds unacceptable above 55 dBA. Sounds had a negligible impact on motorized users. Abstract: Understanding visitor evaluations of human-caused sounds is an essential component to managing recreation experiences in parks and protected areas. In this study, the impact of sounds from natural gas compressors in Pennsylvania State Forests is explored. Using data collected from over 400 onsite visitors, researchers developed a threshold model that shows how visitor experiences change with sounds from natural gas compressors. The threshold model shows that increased sound levels (dBA) from natural gas compressors have a negative impact on visitor experiences. Further segmentation by activity type shows that there is a negligible impact on motorized users and a negative impact on non-motorized visitors. The threshold model shows that sounds from natural gas compressors become unacceptable to non-motorized users at about 55 dBA. The results from this study can be used to help managers of forests plan for high-quality recreational experiences in an era of expanding natural gas extraction.